HUBUNGAN ANTARA PENGETAHUAN, SIKAP DAN PENGARUH TEMAN SEBAYA TERHADAP PERILAKU MENYIMPANG KEARAH LGBT PADA ANGGOTA KARANG TARUNA X DAN Y DI KOTA DEPOK PERIODE JULI 2019 - Inas Hanuniza, (2019)
Population of LBGT in Indonesia estimated 4% of the total Indonesian population. In 2014, there were much cases related to LGBT in Depok City, such as People with HIV / AIDS in Depok City as many as 353 people involved in same sex relationship. Behavior of LGBT also leads other health problems, such as sexually transmitted diseases and psychiatric disorders. The determinations of LGBT behavioural tendency are knowledge, attitudes and peer group influence. A Cross-sectional study was conducted in July 2019 among 50 members of Local Youth Organization X and Y. Participants were obtained by total sampling technique. The data were analyzed using the chi-square test. Test results showed there were correlations between knowledge of LGBT behavior (P = 0.010; 95% CI: 0.182-0.781), attitudes of deviant behavior (P = 0.002; 95% CI: 0.043-0.521), and peers group influences (P = 0.011 95% CI 1,366-14,981). The conclusion is there were correlations between knowledge, attitudes and peers' group influence with LGBT behavioural tendency in members of local youth organization X and Y in Depok City, so an education about LGBT in Depok is necessary.